Tunable magnetism in layered CoPS3 by pressure and carrier doping - Gu, Yue; Zhang, Shuqing; Zou, Xiaolong (Science China materials, 2021)
Despite extensive research on recently discovered layered ferromagnetic (FM) materials, their further development is hampered by the limited number of candidate materials with desired properties. As a much bigger family, layered antiferromagnetic (AFM) materials represent excellent platforms to not only deepen our understanding of fundamental physics but also push forward high-performance spintronics applications. Here, by systematic first-principles calculations, we demonstrate pressure and carrier doping control of magnetic properties in layered AFM CoPS 3 , a representative of transition metal phosphorus trichalcogenides. In particular, pressure can drive isostructural Mott transition, in sharp contrast to other transition metal thiophosphates. Intriguingly, both pressure and carrier doping can realize the long-sought FM half-metallic states with 100% spin polarization percentage, which is good for improving the injection and detection efficiency of spin currents among others. Moreover, the Mott transition is accompanied by instantaneous spin-crossover (SCO) in CoPS 3 , and such cooperative SCO facilitates the implementation of fast-response reversible devices, such as data storage devices, optical displays and sensors. We further provide an in-depth analysis for the mechanisms of FM half-metallicity and SCO. Tunable magnetism in layered AFM materials opens vast opportunities for purposeful device design with various functionalities.